Digital Natives in the Non-Digital University: A Case Study of Polish Higher Educational Institutions from an Educational and Historical Perspective - Jarosław Kinal; Mariola Kinal (Ignatianum University Press, 2023)
According to the theory of technological determinism, the development and popularisation of communication techniques has led to the emergence of two groups of participants in internet discourse: (1) those who have been 'immersed' in the Internet since childhood - digital natives - and (2) those who remember functioning in the offline world - digital immigrants. The main goal of this article is to present the interpenetration of the needs and demands of digital education and the implementation of these demands in the academic environment. The first part of the article presents the main theories related to the topic and attempts to periodise the phenomenon of education at universities undergoing virtualisation. The second part presents research conducted with the use of the CATI method on a sample of 433 students and 133 university teachers concerning the IT revolution at universities related to the SARS-COV2 pandemic and the need to move classes from lecture halls to virtual spaces. The last part of the article answers the hypotheses posed: (1) the initial dysfunctions of the education process in universities were due to the institutions' unpreparedness for the remote environment and (2) in the opinion of the respondents, the remote education process is not as effective as education in a lecture hall. The conclusions of the study indicate that it is necessary to systematically fund research on remote teaching methodology and tools for effective distance learning. In addition to research, it is also advisable to conduct training and continuously implement new practical solutions in the workplace so that the new media serve teachers and students. In order for distance education to be effective, it is necessary to redefine the use of new media, move away from control towards collaboration and allow students to take ownership of the learning process.